Kidney function monitoring in inflammatory bowel disease: The MONITORED consensus. Issue 3 (March 2022) - Guillo, Lucas; Delanaye, Pierre; Flamant, Martin; Figueres, Lucile; Karam, Sabine; Lemoine, Sandrine; Benezech, Alban; Pelletier, Anne-Laure; Amiot, Aurélien; Caron, Bénédicte; Stefanescu, Carmen; Boschetti, Gilles; et al.
Abstract: Background and aims: Patients with inflammatory bowel diseases (IBD) are exposed to drug-related nephrotoxicity and kidney-related extra-intestinal manifestations (EIMs). Patients should be monitored but guidance is lacking in current international recommendations. The objective of the Kidney Function Monitoring in Inflammatory Bowel Disease (MONITORED) initiative was to achieve an expert consensus about monitoring kidney function in IBD. Methods: A literature review was first conducted. Then, an expert consensus meeting, involving 28 attendees representing French-speaking gastroenterologists and nephrologists, was held as part of an academic initiative on May 28, 2021. An anonymous Delphi process was used to discuss and vote on statements. Agreement was defined as at least 75% of participants voting for any one statement. Results: Experts reached consensus on 11 criteria for referral to the nephrologist. Concerning kidney function monitoring, participants unanimously validated the use of serum creatinine with estimation of the glomerular filtration rate via the MDRD or CKD-EPI equations. A blood ionogram and a urine sample with measurement of a protein-to-creatinine ratio were also broadly agreed validated. Experts recommended performing this monitoring at IBD diagnosis, prior introducing a new treatment, and annually for EIMs screening and evaluation of treatment tolerance. An evaluation 3 months after starting mesalamine and then every 6 months was felt necessary, while for biologics an annually monitoring was deemed sufficient. Conclusion: The MONITORED consensus proposed guidelines on how to monitor kidney function in IBD. These recommendations should be considered in clinical practice to preserve kidney function and ensure the best approach to our patients.